To Teach Musical Ornaments and Methods of Their Performance in Teaching "Instrumental Performance and Ensemble Science" to Students of Higher Education Music - Qobiljon Toshtemirov Qubbijonovich (International Journal on Integrated Education, 2021)
The music of each nation and the works created by composers have rich musical ornaments. Without musical ornaments, music cannot have its full content. Musical ornaments not only enrich the melody in all respects, but also play a huge role in revealing its character. Musical ornaments consist of various melismas and kachirims. The author describes the teaching of musical ornaments and methods of their performance in the teaching of "Instrumental performance and ensemble science" to students of higher education music.